Designing power heterojunction bipolar transistors with non-uniform emitter finger lengths to achieve high thermal stability - 金冬月 张万荣 付强 陈亮 肖盈 王任卿 赵昕 (Chinese physics B, 2011)
With the aid of a thermal-electrical model, a practical method for designing multi-finger power heterojunction bipolar transistors with finger lengths divided in groups is proposed. The method can effectively enhance the thermal stability of the devices without sacrificing the design time. Taking a 40-finger heterojunction bipolar transistor for example, the device with non-uniform emitter finger lengths is optimized and fabricated. Both the theoretical and the experimental results show that, for the optimum device, the peak temperature is lowered by 26.19 K and the maximum temperature difference is reduced by 56.67% when compared with the conventional heterojunction bipolar transistor with uniform emitter finger length. Furthermore, the ability to improve the uniformity of the temperature profile and to expand the thermal stable operation range is strengthened as the power level increases, which is ascribed to the improvement of the thermal resistance in the optimum device. A detailed design procedure is also summarized to provide a general guide for designing power heterojunction bipolar transistors with non-uniform finger lengths.